A bibliometric analysis of information seeking patterns in a mobile environment - Anwar, Rully Khairul; Mulyana, Graceline Esterini; Winoto, Yunus (Jurnal Kajian Informasi dan Perpustakaan, 2025)
The pervasive use of mobile devices has fundamentally changed the way individuals seek information, necessitating a clear understanding of evolving user behavior. This study addresses this need by conducting a bibliometric analysis of 219 documents from the Scopus database to comprehensively map the intellectual landscape and research trends in mobile information-seeking patterns. The analysis reveals significant publication growth, peaking in 2018 with 26 articles. Key contributors in this area include Lee Jongwook as the most prolific author and Kontos et al.’s (2014) work as the most influential, evidenced by its high citation count. A prominent thematic finding is the high occurrence of the term 'female' (162 times), highlighting the critical research focus on gender differences. This emphasis is significant, suggesting that gender is a crucial variable shaping mobile information interactions and search strategies. This has direct theoretical implications for refining information behavior models and practical applications for designing more inclusive and targeted mobile services. Additionally, 'quality of life' has emerged as a dominant and current research topic, indicating a shift towards understanding the broader impacts of mobile information access. Collectively, these findings offer a robust overview that can guide future research directions and inform the development of more effective, user-centric mobile information strategies.